2014
DOI: 10.1186/1471-2377-14-15
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness based interventions in multiple sclerosis - a systematic review

Abstract: BackgroundMultiple sclerosis (MS) is a stressful condition; depression, anxiety, pain and fatigue are all common problems. Mindfulness based interventions (MBIs) mitigate stress and prevent relapse in depression and are increasingly being used in healthcare. However, there are currently no systematic reviews of MBIs in people with MS. This review aims to evaluate the effectiveness of MBIs in people with MS.MethodsSystematic searches were carried out in seven major databases, using both subject headings and key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 39 publications
4
123
1
2
Order By: Relevance
“…Median time since diagnosis was 12.0 years (range=1-38).The mean neurological disability score (EDSS) was 6.5 (SD=1.5), which indicates a transition from being ambulant with an assistive device to requiring a wheelchair. Previous mindfulness studies in MS had all cut-off at EDSS score of 6 [11]. The groups were well matched for gender, age, marital status, education, EDSS scores, distress scores and time since diagnosis.…”
Section: Mindfulness Intervention For Multiple Sclerosis 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Median time since diagnosis was 12.0 years (range=1-38).The mean neurological disability score (EDSS) was 6.5 (SD=1.5), which indicates a transition from being ambulant with an assistive device to requiring a wheelchair. Previous mindfulness studies in MS had all cut-off at EDSS score of 6 [11]. The groups were well matched for gender, age, marital status, education, EDSS scores, distress scores and time since diagnosis.…”
Section: Mindfulness Intervention For Multiple Sclerosis 13mentioning
confidence: 99%
“…Controlled trials on mindfulness in MS [11] showed that after the mindfulness training, patients reported improvements in quality of life, depression, fatigue [12,13], standing and dynamic balance [13,14], and reduced fatigue and pain [15].…”
Section: Introduction Multiple Sclerosis (Ms) Affects 23 Million Peomentioning
confidence: 99%
“…The workshop concluded with a demonstration role-play with a participant playing the role of a client with MS. Experiential exercises and self-practice of the ACT processes were emphasized. Resources included ACT interventions can enhance quality of life and physical health and can decrease anxiety and depression in people with various chronic illnesses, including MS. [5][6][7][8] ACT incorporates mindfulness, which can improve quality of life and mental health in people with MS. 9 Importantly, ACT is a transdiagnostic treatment model that can provide relief for multiple life difficulties rather than for a particular disorder.…”
Section: Act Workhopmentioning
confidence: 99%
“…Such factors may serve as a practical barrier to participation in research studies, highlighting the important point that MBIs may need to be adapted to make them more suitable for the wide and varied population of people with MS. For example, the majority of studies thus far have included participants who score at or below 6 on the expanded disability status scale (EDSS) (able to walk up to 100m with a walking aid), and most of these individuals have had relapsing−remitting phenotypes (RRMS). 5 Very little is thus known about if or how MBIs might help people with progressive phenotypes, or with more severe disabilities.…”
mentioning
confidence: 99%
“…A recent systematic review demonstrated a relative paucity of high-quality research, with evidence for effectiveness being limited to improvements in measures for anxiety, depression, health-related quality of life, standing balance, and fatigue. 5 The UK National Institute for Clinical Excellence (NICE) now includes the recommendation of MBIs as one potential treatment for fatigue. 6 A major issue concerning the use of MBIs in healthcare settings is that, despite various models, there is no consensus definition on the construct of mindfulness itself, and further, no one is really sure how they work.…”
mentioning
confidence: 99%